2000
DOI: 10.1046/j.1471-4159.2000.0750634.x
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effects of Interleukin‐6 on Synaptic Plasticity in the Rat Hippocampus Are Associated with an Inhibition of Mitogen‐Activated Protein Kinase ERK

Abstract: Several cytokines have short-term effects on synaptic transmission and plasticity that are thought to be mediated by the activation of intracellular protein kinases. We have studied the effects of interleukin-6 (IL-6) on the expression of paired pulse facilitation (PPF), posttetanic potentiation (PTP), and long-term potentiation (LTP) in the CA1 region of the hippocampus as well as on the activation of the signal transducer and activator of transcription-3 (STAT3), the mitogen-activated protein kinase ERK (MAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
124
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(131 citation statements)
references
References 52 publications
5
124
1
1
Order By: Relevance
“…In this regard, it is important to note that although some groups have reported neuronal expression of most TLRs both in vitro and in vivo (36,37), others have been unable to demonstrate expression of TLR2 on neurons (38). The implication of this finding for the present study is that the mechanism underlying the Pam 3 Csk 4 -induced depression in LTP may result from its ability to release IL-1␤, IL-6, and TNF␣ from glia; each of these inflammatory cytokines has been shown to inhibit LTP (17,39,40).…”
Section: Discussionmentioning
confidence: 60%
“…In this regard, it is important to note that although some groups have reported neuronal expression of most TLRs both in vitro and in vivo (36,37), others have been unable to demonstrate expression of TLR2 on neurons (38). The implication of this finding for the present study is that the mechanism underlying the Pam 3 Csk 4 -induced depression in LTP may result from its ability to release IL-1␤, IL-6, and TNF␣ from glia; each of these inflammatory cytokines has been shown to inhibit LTP (17,39,40).…”
Section: Discussionmentioning
confidence: 60%
“…As evidence, a consistent animal literature shows peripheral IL-6 (whether the result of exogenous administration or in vivo immune challenge) to be associated with increased levels of cytokines in the hippocampus, where IL-6 and IL-6 receptors are expressed abundantly (6)(7)(8). Further, in several animal models, increased levels of hippocampal IL-6 interfere with long-term potentiation (9)(10)(11), neurogenesis (12), and neural plasticity (13,14), which can all impair performance on hippocampal-dependent learning and memory tests (13,(15)(16)(17). Conversely, IL-6 receptor antagonists prevent inflammation-related disruption of hippocampal LTP and ensuing cognitive sequelae (18).…”
Section: Introductionmentioning
confidence: 82%
“…This finding suggests that the early degeneration of LC neurons and their terminals, which will result first in a local but later in an overall NE deficiency, may facilitate the inflammatory reaction in response to Aβ deposition in the AD brain. Given the fact that several inflammatory molecules have been found to impair neuronal functions that contribute to memory formation and consolidation, such as long-term potentiation (20)(21)(22), NE deficits may directly contribute to early neuronal dysfunction by subsequent elevation of inflammatory molecules. Next, it has been shown that proinflammatory cytokines, such as TNFα and IL-1β, can alone or in concert up-regulate the secretion of Aβ by increasing key players of the APP processing (23).…”
Section: Ne Depletion Decreases Microglial Phagocytosis and Recruitmementioning
confidence: 99%